월경성 기흉 2예 - 최영식; Young Sik Choi; 정연수; Yeon Soo Jung; 서석교; Seok Kyo Seo; 김정현; Jeong Hyeon Kim; 정찬경; Chan Kyung Chung (Obstetrics & gynecology science, 2012)
자궁내막증은 난소를 비롯한 골반내에 발생하는 것이 보통이나 장, 신장, 폐, 간, 담낭, 췌장 등의 다양한 부위에서 발생하는 증례가 보고되고 있다. 월경성 기흉(catamenial pneumothorax)은 일반적으로 월경이 시작된 이후 72시간 이내 발생하는 재발성 기흉으로 정의되며, 자발기흉(spontaneous pneumothorax)의 드문 원인 중 하나이다. 저자들은 월경성 기흉 2예를 수술적 치료 후 생식샘자극호르몬방출호르 몬작용제(gonadotropin-releasing hormone agonist)와 함께 프로게스테론 제제 또는 경구피임약을 사용한 약물치료를 통하여 성공적으로 치료하였기에 문헌고찰과 함께 보고하는 바이다. Endometriosis is usually found in pelvic cavity such as in ovary. But, endometriosis has been described in other organs, although rare, such as intestine, kidney, lung, liver, gall bladder, and pancreas. Catamenial pneumothorax is defined as a recurrent pneumothorax within 72 hours of onset of menstruation and it is a rare cause of spontaneous pneumothorax. We, hereby, report two cases of successfully treated catamenial pneumothorax by gonadotrophin releasing hormone agonist with progestin or oral pill after surgical treatment.